EFEK ANTIHIPERGLIKEMIK INFUSA DAUN BENALU KERSEN (Dendrophthoe pentandra L.Miq) PADA TIKUS PUTIH JANTAN YANG DIINDUKSI ALOKSAN - Az Zahra, Fatihah; Subandrate, Subandrate; Safyudin, Safyudin; Sinulingga, Sadakata (Jurnal Fitofarmaka Indonesia, 2022)
Kersen parasite leaves (Dendropthoe pentandra L. Miq) is a type of parasite that is hemiparasitic and contains active compounds, namely, flavonoids, terpenoids and tannins. This compound has benefits as an antihyperglicemic. This study aims to determine the effect of lowering blood glucose levels from the infusion of Kersen parasite leaves (Dendrophthoe pentandra L. Miq) in male rats induced by alloxan. This research is a laboratory experimental study with a randomized preposttest one group design. The study used alloxan-induced male rats which were divided into 3 dosage groups (38 mg / kg, 77 mg / kg, and 154 mg / kg). In the results of the mean blood glucose levels of rats, there was a decrease in blood glucose levels on the 0th day of treatment, on the 7th day after the treatment there was an increase in blood glucose levels and on the 14th day after the treatment there was a decrease in blood glucose levels except in the dose II group and III. In this study, Kersen parasite leaf infusion had no effect on reducing blood glucose levels of alloxan-induced male white rats.